2010
DOI: 10.1016/j.biomaterials.2009.09.100
|View full text |Cite
|
Sign up to set email alerts
|

Polyketal microparticles for therapeutic delivery to the lung

Abstract: Inflammation in the setting of interstitial lung disease (ILD) occurs in the distal alveolar spaces of the lung, which presents significant challenges for therapeutic delivery. The development of aerosolizable microparticles from non-immunogenic polymers is needed to enable the clinical translation of numerous experimental therapeutics that require localization to the deep lung and repeated delivery for optimal efficacy. Polyketals (PK), a family of polymers, have several unique properties that make them ideal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 27 publications
0
46
0
Order By: Relevance
“…As free ODN rapidly diffuse from the lungs into the blood stream, we sought to prolong their pulmonary retention by adsorbing the ODN onto polyketal nanoparticles. Such particles have an excellent in vivo safety profile and form microparticles 1–5 μm in diameter (appropriate for delivery to the distal alveoli by inhalation) when freeze dried (Supplemental Fig 2A) (19;26). Preliminary studies showed that 30 ug of ODN was adsorbed per mg of polyketal microparticle and that 80% of the ODN was released from the microparticles over 48 hr under physiologic conditions (Supplemental Fig 2B/C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As free ODN rapidly diffuse from the lungs into the blood stream, we sought to prolong their pulmonary retention by adsorbing the ODN onto polyketal nanoparticles. Such particles have an excellent in vivo safety profile and form microparticles 1–5 μm in diameter (appropriate for delivery to the distal alveoli by inhalation) when freeze dried (Supplemental Fig 2A) (19;26). Preliminary studies showed that 30 ug of ODN was adsorbed per mg of polyketal microparticle and that 80% of the ODN was released from the microparticles over 48 hr under physiologic conditions (Supplemental Fig 2B/C).…”
Section: Resultsmentioning
confidence: 99%
“…To improve tumor targeting and pulmonary retention, we adsorbed the CpG ODN onto polyketal microparticles previously shown to be safe and efficient for inhalational administration of therapeutic agents (1417). Polyketal nanoparticles are biodegradable and can be formulated into microparticles optimized for delivery to distal bronchi (18;19). When CpG-MP were delivered intra-tracheally to mice with Lewis lung cancer (a model of human NSCLC), they accumulated and persisted in the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Several new acid-sensitive polyketals were reported with good pHdegradable properties, such as PCADK (von Burkersroda et al, 2002), PPADK (Heffernan & Murthy, 2005) and PK3 (Fiore et al, 2010), that can be used to intracellular drug delivery. However, it is difficult to obtain the polyketal polymers.…”
Section: Discussionmentioning
confidence: 99%
“…10~15 μm and an over 50 days active durative [45]. However, their size exceeded the circulation limit of less than 500nm in diameter and they are often been cleared rapidly due to retention in the microvasculature [46]. At the same time, the small (<20 nm) volume of nanocarriers usually extravasated via vascular pores and retained in parenchymal cells.…”
Section: Loading Capacity and Nanocarrier Volumementioning
confidence: 98%